Pembuatan Game RPG Multiplayer Online Berbasis Android - Ryan Hosea; Gregorius Satia Budhi; Leo Willyanto Santoso (Jurnal Infra, 2017)
Gadget is important now, children of all ages already understand how to use gadgets. This resulted in more children often spend time playing the current gadget. By providing entertainment through games application, so users can be entertained. The application consists of 5 menu that map, shop, inventory, character, and tournaments. On the menu map players can carry out the mission and receive a gift. In the shop menu, players can view and purchase goods. On the inventory menu, players can see the items that are owned and can sell it. On the menu character, players can replace equip and improve skills. On the menu tournament, players can challenge other players to be matched with a character of its own. Overall, the application is able to create and display the mission, as well as be able to give levels to players with a rating. Players can also increase the ability of the characters to wear equip and improve skills.